2017
DOI: 10.3390/sports5020040
|View full text |Cite
|
Sign up to set email alerts
|

Active Recovery between Interval Bouts Reduces Blood Lactate While Improving Subsequent Exercise Performance in Trained Men

Abstract: This study aimed to examine the blood lactate and blood pH kinetics during high-intensity interval training. Seventeen well-trained athletes exercised on two different occasions. Exercises consisted of three 30 s bouts at a constant intensity (90% of peak power) with 4 min recovery between bouts followed by a Wingate test (WT). The recoveries were either active recovery (at 60% of the lactate threshold intensity) or passive recovery (resting at sitting position). During the exercise, blood samples were taken t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 25 publications
2
12
0
Order By: Relevance
“…Our findings show that ACT recovery has a better effect on repeated-sprint performance than PAS recovery or LFES. It is in accordance with several studies where ACT recovery better influenced performance or lactate removal than PAS recovery in different types of exercise [1][2][3][4][5][6][7][8][9][10][11].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings show that ACT recovery has a better effect on repeated-sprint performance than PAS recovery or LFES. It is in accordance with several studies where ACT recovery better influenced performance or lactate removal than PAS recovery in different types of exercise [1][2][3][4][5][6][7][8][9][10][11].…”
Section: Discussionsupporting
confidence: 91%
“…Active (ACT) and passive (PAS) are two commonly used recovery modalities. Several studies showed that ACT recovery had a better effect on performance than PAS recovery in different types of exercise [1][2][3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Intermittent exercise, which consists of repeated sets of exercise separated by periods of recovery, is suggested to produce comparable physiological adaptations to continuous exercise [13,19]. During intermittent exercise, lactate production also follows an intermittent pattern [20]. Therefore, to examine if intermittent exposure to lactate has the potential to induce mitochondrial adaptations, we cultured C2C12 myotubes for 2 h, but by changing the medium every 15 min (DM supplied with different concentrations of L-lactate; see Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Further confounding this issue is the active or passive nature of the HIIT/SIT recovery, as some studies do not sufficiently standardize the periods in between work bouts, allowing some participants complete rest while others perform active recovery. With regard to traditional Wingate‐based SIT, these periods account for >85% of the protocol duration, and differences between active or passive recovery may impact the return of trueV˙O 2 to resting values, as directly evidenced by recent work using a Wingate‐based SIT protocol . The degree to which the various protocols, including rest/recovery periods, are administered as planned or standardized across individuals is not often reported and, as such, warrants the question of whether the EPOC observed is due to methodological inconsistencies with measurement, or due to the protocol administration itself.…”
Section: Methodological Inconsistencies and Limitationsmentioning
confidence: 99%